2020
DOI: 10.14336/ad.2019.0616
|View full text |Cite
|
Sign up to set email alerts
|

Management of The Elderly Cancer Patients Complexity: The Radiation Oncology Potential

Abstract: Radiation oncology has the potential to be an excellent option for the frail elderly cancer patients because of its limited systemic toxicities. It can be effective for curative, prophylactic, disease control or palliative purposes. Currently about 60% of all cancer patients undergoing active treatment at some point receive radiation treatment. However, though widely used, there are limited clinical trials strictly designed for the elderly. This paper will review the key points in the assessment and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…In all our sample, the treatment more frequently proposed was, of course, radiotherapy, since our population belongs to this Unit. The high number of oldest old patients treated with radiotherapy confirms the evidence that this is an ideal therapy for older adults [ 12 , 13 ]. The second more frequent treatment was hormone therapy, because of the large prevalence of breast and prostate cancer.…”
Section: Discussionmentioning
confidence: 73%
“…In all our sample, the treatment more frequently proposed was, of course, radiotherapy, since our population belongs to this Unit. The high number of oldest old patients treated with radiotherapy confirms the evidence that this is an ideal therapy for older adults [ 12 , 13 ]. The second more frequent treatment was hormone therapy, because of the large prevalence of breast and prostate cancer.…”
Section: Discussionmentioning
confidence: 73%
“…The CGA approach is considered essential to identify problems that are not immediately evident. Several studies have demonstrated the ability of CGA to identify otherwise unrecognized conditions of vulnerability to support the decision-making of the specialist (oncologist, radiotherapist, surgeon) when estimating the risk of toxicity to prevent said toxicity and preserve the functional performance of patients [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the elderly and frail population, the longer schedule of treatment is related to poor compliance 14 and a moderate hypofractionated proton beam allowed us to condense the overall treatment time. Literature reports that other reasons why the geriatric population tends to decline RT are the idea of being too old to undergo RT treatment, fear of worsened quality of life, loss of independence due to RT-related toxicities, and inadequate communication with the physician.…”
Section: Discussionmentioning
confidence: 99%